Пошаговое объяснение:
|5х+3|-3х=|5*(-8)+3|-3(-8)=|-40+3|+24=|-37|+24=37+24=61
|5х + 3| - 3х
х = -8
Подставим значение переменной, вспомнив при этом, что значение из-под модуля всегда больше или равны нулю:
|5 · (-8) + 3| - 3 · (-8) =
= |-40 + 3| + 24 =
= |-37| + 24 =
= 37 + 24 = 61
ответ: 61.
Пошаговое объяснение:
|5х+3|-3х=|5*(-8)+3|-3(-8)=|-40+3|+24=|-37|+24=37+24=61
|5х + 3| - 3х
х = -8
Подставим значение переменной, вспомнив при этом, что значение из-под модуля всегда больше или равны нулю:
|5 · (-8) + 3| - 3 · (-8) =
= |-40 + 3| + 24 =
= |-37| + 24 =
= 37 + 24 = 61
ответ: 61.